Local factor H production by human choroidal endothelial cells mitigates complement deposition: implications for macular degeneration. Issue 1 (17th February 2022) - Mulfaul, Kelly; Mullin, Nathaniel K; Giacalone, Joseph C; Voigt, Andrew P; R DeVore, Melette; Stone, Edwin M; Tucker, Budd A; Mullins, Robert F
Abstract: Activation of the alternative complement pathway is an initiating event in the pathology of age‐related macular degeneration (AMD). Unchecked complement activation leads to the formation of a pro‐lytic pore, the membrane attack complex (MAC). MAC deposition is observed on the choriocapillaris of AMD patients and likely causes lysis of choroidal endothelial cells (CECs). Complement factor H (FH, encoded by the gene CFH ) is an inhibitor of complement. Both loss of function of FH and reduced choroidal levels of FH have been reported in AMD. It is plausible that reduced local FH availability promotes MAC deposition on CECs. FH is produced primarily in the liver; however, cells including the retinal pigment epithelium can produce FH locally. We hypothesized that CECs produce FH locally to protect against MAC deposition. We aimed to investigate the effect of reduced FH levels in the choroid to determine whether increasing local FH could protect CECs from MAC deposition. We demonstrated that siRNA knockdown of FH ( CFH ) in human immortalized CECs results in increased MAC deposition. We generated AMD iPSC‐derived CECs and found that overexpression of FH protects against MAC deposition. These results suggest that local CEC‐produced FH protects against MAC deposition, and that increasing local FH protein may be beneficial in limiting MAC deposition in AMD. © 2022 The Pathological Society of Great Britain and Ireland.